Ionic Association of Potassium and Tetrabutylammonium Thiocyanate Salts in Binary Mixtures of γ-Butyrolactone and N,N-Dimethylacetamide at 298.15 K and 308.15 K - Kumar, Suresh; Anand, Hardeep (Asian Journal of Chemistry, 2022)
Solvation consequences of potassium thiocyanate (KSCN) and tetrabutylammonium thiocyanate (Bu4NSCN) in γ-butyrolactone (GBL), N,N-dimethylacetamide (DMA) and their binary mixtures in concentration range (0.01-0.001) mol Kg–1 of 0, 25, 50, 60, 80 and 100 mol% DMA at T = 298.15 K and 308.15 K have been studied using conductometric study and some samples of KSCN in GBL + DMA binary mixtures of different electrolytic concentrations at ambient conditions studied by FTIR spectroscopic methods. The Shedlovsky equation has been used to elucidate the data in terms of the limiting molar conductances (Λo), ion-pair association constants (KA). The Walden products (Λoho), solvated radii (ri) and standard free energies of association (ΔGºA) were further evaluated in terms of solvation of ions. The reference electrolyte tetrabutylammonium tetraphenylborate (Bu4NBPh4) was used to determine the limiting molar ionic conductances. In pure solvents and their binary mixtures, electrolytes showed a strong association. The K+ ions have greater solvation in GBL than in DMA observed on basis of solvated radii in GBL + DMA binary solvent mixtures at both experimental temperatures. The study demonstrates that the ion-solvent interactions decrease on enhancing the temperature. The FTIR analysis was applied to obtain information about molecular as well as ionic association of KSCN in GBL + DMA binary mixtures at the ambient conditions, which has provided the information on structuring infrared modes of vibrational stretching frequencies according to the nature of the solvents or the cations. Shifting of vibrational frequencies of several functional groups of DMA and GBL in binary mixed solvents has been observed in terms of ion-ion, ion-solvent and solvent-solvent interactions.